Development of Method for Service Support Management in Vehicular Communication Networks - Mindaugas Kurmis; Miroslav Voznak; Gintaras Kucinskas; Darius Drungilas; Zydrunas Lukosius; Sergej Jakovlev; Arunas Andziulis (Advances in Electrical and Electronic Engineering, 2017)
In this work, the method and prototype for managing the quality of wireless communication channel is presented. The proposed methodology, based on multi-criteria information utility assessment process, is designed. The heterogeneous context awareness data collection subsystems integration is enabled by transforming the acquired data to the highly dynamic intelligent transport systems. Each element of this intellectual transport system runs as a separate component having a specific environmental monitoring and control elements. Evaluation of context information utility allowed realizing the methods and algorithms that adaptively reduce the load on the wireless channel, and the transmitted and stored data volume without losing the enriched contextual information quality, which allows developing more complex heterogeneous services. It is believed that the obtained scientific results will have positive effect for the future research and development of context awareness and service adaptation systems.